2006
DOI: 10.1016/j.heares.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear microdialysis for quantification of dexamethasone and fluorescein entry into scala tympani during round window administration

Abstract: Before new drugs for the treatment of inner ear disorders can be studied in controlled clinical trials, it is important that their pharmacokinetics be established in inner ear fluids. Microdialysis allows drug levels to be measured in perilymph without the volume disturbances and potential cerebrospinal fluid contamination associated with fluid sampling. The aims of this study were to show: (i) that despite low recovery rates from miniature dialysis probes, significant amounts of drug are removed from small fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 44 publications
10
42
0
3
Order By: Relevance
“…The method of animal preparation and drug application is described in detail elsewhere (19). In brief, nine specific pathogen free guinea pigs (mean weight: 423g; 300-600g; Charles River, Kißlegg, Germany) were anesthetized by intraperitoneal injection of an initial dose of 8 mg/ kg xylazine (Bayer, Leverkusen, Germany) plus 140 mg/kg ketamine hydrochloride (Pharmacia & Upjohn, Erlangen, Germany).…”
Section: Animal Preparation and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of animal preparation and drug application is described in detail elsewhere (19). In brief, nine specific pathogen free guinea pigs (mean weight: 423g; 300-600g; Charles River, Kißlegg, Germany) were anesthetized by intraperitoneal injection of an initial dose of 8 mg/ kg xylazine (Bayer, Leverkusen, Germany) plus 140 mg/kg ketamine hydrochloride (Pharmacia & Upjohn, Erlangen, Germany).…”
Section: Animal Preparation and Proceduresmentioning
confidence: 99%
“…Anesthesia was maintained by repeated intramuscular injections of 25-33% of the initial dose. Further preparation followed as described in Hahn et al (2006) and in Figure 1. The animal experiments were approved by the animal studies committee of the University of Tübingen.…”
Section: Animal Preparation and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous pharmacokinetic studies of locally-applied corticosteroids in animals (Nomura 1984;Parnes et al 1999;Chandrasekhar et al 2000;Bachmann et al 2001;Hahn et al 2006Hahn et al , 2012Liu et al 2006;Plontke et al 2008b;Yang et al 2008;Wang et al 2009;Borden et al 2011;Salt et al 2011a) and humans (Bird et al 2007;Bird et al 2011), but only a subset of these studies has been analyzed quantitatively to derive an elimination rate. Plontke and analyzed prednisoline data of Bachmann et al (2001) from guinea pigs and found it to be consistent with an elimination half-time from perilymph of 130 min.…”
Section: Introductionmentioning
confidence: 99%
“…Although many substances can be applied to the round window membrane (RWM) and from there diffuse into perilymph, large or anionic molecules do not easily permeate the RWM (Goycoolea and Lundman, 1997). In addition, pharmacokinetic studies suggest that there is considerable variation in the permeability of the RWM in different animals, resulting in highly variable drug levels in perilymph (Chelikh et al, 2003,Hahn et al, 2006,Mynatt et al, 2006,Plontke et al, 2007. To overcome these problems, an alternative approach is to inject the drug or other substance directly into the inner ear fluids.…”
Section: Introductionmentioning
confidence: 99%